Juvenile Residential Facility Census, 2014 (United States) ([Verlag nicht ermittelbar], 2016)
The Juvenile Residential Facility Census (JRFC), which is conducted biennially, collects basic information on juvenile residential facility characteristics, including security, capacity and crowding, injuries and deaths in custody, and facility ownership and operation. The JRFC also includes questions about facility type (such as detention center, training school, ranch, or group home) and residential services provided by the facility (such as independent living, foster care, or other arrangements), and detailed questions about mental health, substance abuse, and educational services provided to young persons. In 2014, the JRFC was divided into seven sections: General facility information Mental health services Educational services Substance abuse services Events in the 30 days prior to the census reference date Deaths in the year prior to the census reference date Space shared with other facilities Congress requires the Office of Juvenile Justice and Delinquency Prevention (OJJDP) to report annually on the number of deaths of juveniles in custody; the JRFC gathers this information and offers a portrait of the nation's juvenile facilities. The census reference date was the fourth Wednesday in October.